2007
DOI: 10.1071/sr06077
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of different land use and soil management on various organic carbon fractions in an Inceptisol of subtropical India

Abstract: Land use changes, especially the conversion of native forest vegetation to cropland and plantations in tropical regions, can potentially alter soil C dynamics. A study was conducted to assess the effects of various land uses and soil managements (agro-forestry plantation, vegetable field, tube-well irrigated rice–wheat, sewage-irrigated rice–wheat, and uncultivated soils) on soil pH, bulk density, soil organic C (SOC), particulate organic C (POC), microbial biomass C (MBC), C mineralisation (Cmin), microbial q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Variations in C and N stocks can be caused by different C inputs from biomass leftovers (Purakayastha et al . 2007), although return of crop residues to fields is threatened by competing uses as some farmers collect and store the crop residues for livestock feed over the dry season. If left in the field, existing policies allow free-range livestock grazing over the dry period (Rufino et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in C and N stocks can be caused by different C inputs from biomass leftovers (Purakayastha et al . 2007), although return of crop residues to fields is threatened by competing uses as some farmers collect and store the crop residues for livestock feed over the dry season. If left in the field, existing policies allow free-range livestock grazing over the dry period (Rufino et al .…”
Section: Discussionmentioning
confidence: 99%
“…Bremer et al (1994) and Eghball & Ginting (2003) found the application of manure and compost to have significant C sequestration effects while chemical fertilizers had no effect. Variations in C and N stocks can be caused by different C inputs from biomass leftovers (Purakayastha et al 2007), although return of crop residues to fields is threatened by competing uses as some farmers collect and store the crop residues for livestock feed over the dry season. If left in the field, existing policies allow free-range livestock grazing over the dry period (Rufino et al 2011), threatening the persistence of residues in the fields.…”
Section: Carbon and Nitrogen In Bulk Soilmentioning
confidence: 99%
“…Soil organic C dynamics can be influenced by climate and land-use changes (Schlesinger 1990;Paul et al 1997;IPCC 2001;Purakayastha et al 2007) and soil management practices (Matson et al 1997;Blumfield et al 2006;Xu and Chen 2006;Xu et al 2008a, b). There is much concern that land-use change may have significant feedbacks on the global C cycle (Batjes and Sombroek 1997;Post and Kwon 2000).…”
mentioning
confidence: 98%
“…Active soil organic carbon is easily and directly used by organisms. It is active and most sensitive to physical and chemical disturbances (Purakayastha et al, 2007). These SOC fractions are also important for nutrient cycle.…”
mentioning
confidence: 99%